RASIONALISASI PENATAAN KELEMBAGAAN PEMERINTAH DAERAH - Joni Dawud (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2007)
Through local autonomy, local governments are expected to shape a rational institutionalstructure based upon local needs. However, it reveals that local government structure hasbecome more ineffective and inefficient. Having known this, necessities for structuredownsizing should be voiced to meet the real local needs.